Creating a Community of Practice to Prevent Suicide Through Multiple Channels: Describing the Theoretical Foundations and Structured Learning of PC CARES. (January 2016) - Wexler, Lisa; McEachern, Diane; DiFulvio, Gloria; Smith, Cristine; Graham, Louis F.; Dombrowski, Kirk
It is critical to develop practical, effective, ecological, and decolonizing approaches to indigenous suicide prevention and health promotion for the North American communities. The youth suicide rates in predominantly indigenous small, rural, and remote Northern communities are unacceptably high. This health disparity, however, is fairly recent, occurring over the last 50 to 100 years as communities experienced forced social, economic, and political change and intergenerational trauma. These conditions increase suicide risk and can reduce people's access to shared protective factors and processes. In this context, it is imperative that suicide prevention includes—at its heart—decolonization, while also utilizing the "best practices" from research to effectively address the issue from multiple levels. This article describes such an approach: Promoting Community Conversations About Research to End Suicide (PC CARES). PC CARES uses popular education strategies to build a "community of practice" among local and regional service providers, friends, and families that fosters personal and collective learning about suicide prevention in order to spur practical action on multiple levels to prevent suicide and promote health. This article will discuss the theoretical underpinnings of the community intervention and describe the form that PC CARES takes to structure ongoing dialogue, learning, solidarity, and multilevel mobilization for suicide prevention.